Management Sustainable Antenatal Care Service in A Post Covid-19 Disruption - Teguh Setiawan Wibowo; Fitria (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Covid-19 pandemic affects maternal health both directly and indirectly and these direct and indirect effects are interrelated. This is indicated by the restrictions that are carried out on almost all routine services, including Antenatal Care services, where pregnant women do not want to go to the puskesmas or other health care facilities. Pregnant women are afraid of contracting the Covid-19 virus and the unpreparedness of health services in terms of personnel and infrastructure, including personal protective equipment, is the reason that pregnant women prefer to postpone pregnancy checks and classes for pregnant women. So that Antenatal Care services can still be carried out in order to fulfill the community's right to basic health, especially for pregnant women after the Covid-19 disruption, the Indonesian government needs to start new habits and provide new guidelines for health services, especially pregnant women so that they can adapt to new habits and keep getting essential services needed. In this article, the discussion will focus on the management of Antenatal Care services in a sustainable manner after the Covid-19 disruption.